The Smarāgamā as Dialogical Theology: Hindu-Islamic Convergence in Bali - Ida Bagus Subrahmaniam Saitya; Lalu Usman Ali; Mawardi Saleh; Made Wahyu Mahendra (Jurnal Penelitian Agama Hindu, 2026)
This study examines the articulation of Islamic and Hindu theological concepts in the Smarāgamā, a Balinese lontar manuscript that reflects interreligious encounters in pre-modern Bali. While previous studies on Hindu-Muslim relations in Bali have largely focused on sociological practices and cultural coexistence, the theological and textual dimensions of these encounters remain critically underexplored. Drawing on the scholarly transliteration and translation edition by Manuaba et al., (2017) as its primary source, this research employs qualitative textual and contextual analysis to investigate how key Islamic concepts, Allah, makrifat, and hakikat are systematically articulated within a Hindu Śaiva metaphysical framework. The findings reveal that Smarāgamā does not position Islam and Hinduism as competing systems; rather, it constructs a dialogical theological framework in which Islamic Sufi epistemology and Hindu Śaiva metaphysics converge through shared principles of tattwa eka (divine unity), spiritual knowledge, and ethical discipline. Four principal findings emerge from this study: first, the text constructs a shared metaphysical ground between Hyang Widhi and Allah as expressions of the same transcendent reality; second, the Islamic Sufi concepts of makrifat, hakikat, and nur function as epistemological bridges connecting Islamic and Hindu spiritual traditions through analogical rather than identical relationships; third, the text develops an interreligious cosmology through the internalization of Mecca as inner sacred geography and the embodiment of the Islamic prophetic tradition within the Hindu microcosmic understanding of the human body and fourth, the text foregrounds ethical conduct and inner purification as universal prerequisites for divine knowledge, transcending formal religious boundaries. Taken together, these findings demonstrate that Smarāgamā represents a localized yet intellectually sophisticated model of dialogical theology, organically emerging from within the Hindu Śaiva tradition of Bali, evidence that inclusive and dialogical interreligious perspectives have deep historical roots in Balinese intellectual heritage, with meaningful implications for comparative theology and interreligious studies in the Indonesian context.